Possible Mechanisms for Maintenance and Regression of Corpus Luteum Through the Ubiquitin-Proteasome and Autophagy System Regulated by Transcriptional Factors - Teeli, Aamir S.; Leszczyński, Paweł; Krishnaswamy, Narayanan; Ogawa, Hidesato; Tsuchiya, Megumi; Śmiech, Magdalena; Skarzynski, Dariusz; Taniguchi, Hiroaki (Frontiers in Endocrinology, 2019)
The corpus luteum (CL) is an important tissue of the female reproductive process which is established through ovulation of the mature follicle. Pulsatile release of prostaglandin F2α from the uterus leads to the regression of luteal cells and restarts the estrous cycle in most non-primate species. The rapid functional regression of the CL, which coincides with decrease of progesterone production, is followed by its structural regression. Although we now have a better understanding of how the CL is triggered to undergo programmed cell death, the precise mechanisms governing CL protein degradation in a very short period of luteolysis remains unknown. In this context, activation of ubiquitin-proteasome pathway (UPP), unfolded protein response (UPR) and autophagy are potential subcellular mechanisms involved. The ubiquitin-proteasome pathway (UPP) maintains tissue homeostasis in the face of both internal and external stressors. The UPP also controls physiological processes in many gonadal cells. Emerging evidence suggests that UPP dysfunction is involved in male and female reproductive tract dysfunction. Autophagy is activated when cells are exposed to different types of stressors such as hypoxia, starvation, and oxidative stress. While emerging evidence points to an important role for the UPP and autophagy in the CL, the key underlying transcriptional mechanisms have not been well-documented. In this review, we propose how CL regression may be governed by the ubiquitin-proteasome and autophagy pathways. We will further consider potential transcription factors which may regulate these events in the CL.